Evaluating the impact of organic compost on soil microbial diversity in sustainable Malaysian agriculture: a review/ Effonny Sandra Denil, Rozlianah Fitri Said and Hendry Joseph - Denil, Effonny Sandra; Said, Rozlianah Fitri; Joseph, Hendry (Universiti Teknologi MARA, Sabah, 2024)
The excessive use of chemical fertilisers in agriculture has led to a trend of soil degradation, particularly affecting agricultural farming in Malaysia. While chemical fertilisers offer rapid, shortterm increases in crop yield, their long-term detrimental effects on soil health and the environment are becoming increasingly apparent. These fertilisers disrupt vital soil microbial diversity, leading to a decrease in soil fertility over time. To counteract these issues, the practice of using organic compost has emerged as a sustainable alternative in agriculture. Organic compost not only improves soil structure but also provides vital nutrients and encourages microbial activity in plant crops. While various studies have compared the impact of different types of organic compost on crop growth, there is currently limited local research focused on the presence and diversity of soil microbial communities in sustainable crop production in Malaysia. This review aims to provide scholars and practitioners, particularly in Malaysia, with a thorough understanding of the benefits and applications of organic compost and its impact on soil microbial diversity for sustainable agriculture.